ANALISIS PERGUDANGAN DI BAGIAN GUDANG BARANG JADI (FINISHGOODS) PT NIPRESS TBK CILEUNGSI BOGOR - Nurmaliana Yusuf; Yevita Nursyanti (Politeknik APP Jakarta, 2017)
This research was made aiming to determine the work processes in the warehouse of finished goods, which has a main activity that is in the process of receiving, storing and shipping goods, especially in the warehouse of finished. This research was conducted by analyzing the actual conditions are compared to a SOP (Standard Operating Procedure) and Work Instructions. An SOP (Standard Operating Procedure) is made and documented in writing containing procedure or workflow to be achieved by a company or institution. In addition to analyzing the main activities of the warehouse, ths research also analyzes the process palletize (roll battery), standard processes FIFO (First In First Out), and also the process of inventory taking which three are in the process of storage of finished goods. This analysis included descriptive comparative analysis by comparing the actual conditions in the finished goods warehouse with a procedure and work instructions. The results of this analysis is the process activity finished goods warehouse of the receipt, storage, inventory taking, and local delivery is not in accordance with the procedures and work instructions are there, but a standard process FIFO (First In First Out), and the process palletize (rolls battery) has been carried out in accordance with the procedures and work instructions finished goods warehouse